HIBISCUS ROSA-SINENSIS MUCILAGE AS A FUNCTIONAL POLYMER IN PHARMACEUTICAL APPLICATIONS: A REVIEW - YAHAYA, NURUL AIMAN; ANUAR, NOR KHAIZAN; SAIDIN, NOR MAZIAH (International Journal of Applied Pharmaceutics, 2023)
The administration of drugs into the body is essential for the treatment of diseases. However, drugs need to reach the targeted site to be effective. Excipients such as polymers are used in drug formulations to ensure that drugs exert their therapeutic effects. Recently, plant-based polymers have been extensively explored in pharmaceutical research. These polymers, including gums and mucilages, are investigated for their roles in various pharmaceutical applications. The plant-based polymers have advantages compared to synthetic polymers due to their bioavailability, chemical inertness, non-toxicity and wide availability. When gums or mucilages are combined with other polymers, their final properties improve. In some instances, the characteristics of gums and mucilages such as swelling, flow and mucoadhesive properties are better than the abilities of synthetic materials. This article reviews the use of Hibiscus rosa-sinensis (HRS) mucilage as an excipient in several dosage forms to enhance drug delivery systems. Their physicochemical properties and mechanisms of action are also discussed. The review ends with a discussion of the limitations and future prospects of HRS mucilage in pharmaceutical applications.